Peranan Ibu Terhadap Anak dalam Pendidikan Islam di Era Globalisasi - Nisak, Khoirun (JOEAI (Journal of Education and Instruction), 2022)
This study aims to describe the role of mothers towards children in Islamic education in the era of globalization. This research is classified as library research, namely research carried out using literature. The data collection technique is to conduct a review study of books, records, and reports that have to do with the problem being solved. Analysis of the data is by searching, collecting and examining more deeply from various materials or references related to the problems in this research, and then drawing conclusions, namely explaining the descriptions of the data in several sentences containing a brief and concise understanding. The results of the study indicate that the role of mothers towards children in Islamic education in the era of globalization is very important to continue to be considered and intensified. Because seeing the era of globalization which is full of various kinds of challenges and threats that arise due to the development of increasingly sophisticated technology. In conclusion, based on the results of the study obtained information, namely, the role of the mother as an educator, the role of the mother as a guide, the role of the mother as a caregiver or nurse, the role of the mother as a source of affection, the role of the mother as a motivator and the role of the mother as a role model for children. Keywords: Globalization Era. The Role of Mothers, Islamic Education